STORAGE OF AUSTRALIAN ROYAL PALM (Archontophoenix cunninghamii H. Wendl. & Drude) SEEDS - LUZ, Petterson Baptista da; PIVETTA, Kathia Fernandes Lopes (Scientia Agraria, 2010)
Archontophoenix cunninghamii H.Wendl. & Drude, popularly known as Australian Royal Palm, is an exotic palm frequently used in landscaping. Recently it has great interest on palm heart producing, increasing seedlings demand. With the aim of evaluating the seeds viability of A. cunninghamii during the storage, they were packed in polyethylene transparent bags and placed in cold room (temperature of 10 °C and relative moisture between 62% to 65%) for 11 months. The statics design adopted was completely randomized with four repetitions of 25 diaspores. For germination test, seeds were packed into plastic boxes containing the substrate vermiculite and placed in BOD-type germination chambers at controlled and alternating temperature of 25-35 °C and photoperiod of 16 hours. The germination data was taken daily until the stabilization of the germination, using the appearance of the seed protrusion as criterion for the stabilization. The germination percentage and germination speed index were determined and the analysis of polynomial regression was performed. It was concluded that the storage, packed in polyethylene and cold kept the moisture content of seeds, and efficient for the preservation of its quality and storage time affected the germination percentage and speed.